2015
DOI: 10.4172/1948-5956.1000322
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 Functions as a Tumor Suppressor by Inhibiting Epithelial to Mesenchymal Transition in Ovarian Cancer

Abstract: Objective Ovarian cancer is a gynecological malignancy that has a high mortality rate in women due to metastatic progression and recurrence. miRNAs are small, endogenous, noncoding RNAs that function as tumor suppressors or oncogenes in various human cancers by selectively suppressing the expression of target genes. The objective of this study is to investigate the role of miR-203 in ovarian cancer. Methods miR-203 was expressed in ovarian cancer SKOV3 and OVCAR3 cells using lentiviral vector and cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
(54 reference statements)
5
24
0
Order By: Relevance
“…While STAT1 expression is markedly lower in cells with enforced miR203 expression, both STAT2 and STAT3 are unaffected by miR203 expression (Figure 4A). Moreover, while STAT1 was a miR203 target gene in GBM cells, as shown in Figure 4B Snai2/Slug was not consistently silenced by miR203 expression in GBM cells, although it was targeted by miR203 in ovarian cancer cells [34]. This finding is also consistent with our previous findings that miRNAs silence gene expression in a cell-type specific manner.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…While STAT1 expression is markedly lower in cells with enforced miR203 expression, both STAT2 and STAT3 are unaffected by miR203 expression (Figure 4A). Moreover, while STAT1 was a miR203 target gene in GBM cells, as shown in Figure 4B Snai2/Slug was not consistently silenced by miR203 expression in GBM cells, although it was targeted by miR203 in ovarian cancer cells [34]. This finding is also consistent with our previous findings that miRNAs silence gene expression in a cell-type specific manner.…”
Section: Resultssupporting
confidence: 91%
“…While oncogenic miRNAs have been studied in depth, tumor suppressor miRNAs which tend to be underexpressed in cancer have been relatively poorly characterized. We recently identified miR203 to have tumor suppressive activity in ovarian cancer by targeting Slug/snail2 and inhibiting epithelial to mesenchymal transition [34]. In the present study we found that miR203 was expressed at especially low levels in GBM.…”
Section: Introductionsupporting
confidence: 60%
“…We previously demonstrated that miR-203 is a tumor suppressor miRNA in ovarian cancer and that miR-203 expression inhibits tumor growth by targeting transcription factor Snai2 [ 23 ]. We also showed that BIRC5/survivin was highly expressed in ovarian cancer but not in the normal ovary tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistent findings have also been reported. For example, miR-124-3p, miR-148a-3p, miR-203a, and miR-375 were detected exhibiting differential expression in EOC specimens with both downregulation and upregulation [ 114 , 116 , 117 , 118 , 119 ]. Several other miRNAs listed in Table 1 have also been shown to be either up- or down-regulated in different studies.…”
Section: Dysregulation Of Mirna Expression In Ovarian Cancermentioning
confidence: 99%
“…Overexpression of miR-101-3p, miR-130b, and miR-1236-3p inhibits EOC cell invasion and migration, increases E-cadherin, and decreases mesenchymal markers by directly targeting ZEB1 [ 165 , 168 , 178 ]. Similarly, SNAI1 and SNAI2 are targets of multiple miRNAs [ 119 , 167 , 175 , 222 ]. Using the TCGA database and tissue samples from EOC patients, Yang et al identified miR-506 as a positive prognostic predictor of EOC patients [ 222 ].…”
Section: Roles Of Mirnas In Ovarian Cancer Metastasismentioning
confidence: 99%